2020
DOI: 10.1021/acsomega.0c02699
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Iron Nanocubes Effectively Capture Epithelial and Mesenchymal Cancer Cells

Abstract: Current methods for capturing circulating tumor cells (CTCs) are based on the overexpression of cytokeratin (CK) or epithelial cell-adhesion molecule (EpCAM) on cancer cells. However, during the process of metastasis, tumor cells undergo epithelial-to-mesenchymal transition (EMT) that can lead to the loss of CK/EpCAM expression. Therefore, it is vital to develop a capturing technique independent of CK/EpCAM expression on the cancer cell. To develop this technique, it is important to identify common secondary o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 56 publications
(121 reference statements)
0
4
0
Order By: Relevance
“… 103 However, for a significant fraction of patients, this system may lead to inherently EpCAM-negative and epithelial-to-mesenchymal transition (EMT) inverted CTCs being ignored. 99 , 100 In order to improve the accuracy of CTCs detection, Chen et al constructed IONPs loaded magnetic immunoliposomes (MIL) linked with one of the four kinds of antibodies (EpCAM, EGFR, HER-2 and mucin-1) ( Figure 6A ). 28 The results indicated that the cumulative CTCs-positive rate was up to 87.5% with four different magnetic nanoparticles, which is much higher than that of any single magnetic nanoparticles and their mixed counterpart ( Figure 6B ).…”
Section: Application Of Ionps In Guiding Tumor Therapy and Evaluating...mentioning
confidence: 99%
See 2 more Smart Citations
“… 103 However, for a significant fraction of patients, this system may lead to inherently EpCAM-negative and epithelial-to-mesenchymal transition (EMT) inverted CTCs being ignored. 99 , 100 In order to improve the accuracy of CTCs detection, Chen et al constructed IONPs loaded magnetic immunoliposomes (MIL) linked with one of the four kinds of antibodies (EpCAM, EGFR, HER-2 and mucin-1) ( Figure 6A ). 28 The results indicated that the cumulative CTCs-positive rate was up to 87.5% with four different magnetic nanoparticles, which is much higher than that of any single magnetic nanoparticles and their mixed counterpart ( Figure 6B ).…”
Section: Application Of Ionps In Guiding Tumor Therapy and Evaluating...mentioning
confidence: 99%
“…Due to its excellent magnetic behavior (>40 emu/g) and easy construction, antibody-modified IONPs can be used for magnetic immunization separation and detection of certain cell populations from biological suspensions. 28,[99][100][101] Briefly, modified IONPs can specifically bind to corresponding receptors on the surface of CTCs and thus isolate CTCs in an external magnetic field. Then, CTCs could be detected through FI or micro-MRI technology.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…The suspension was then sonicated for 10 min, and nitrogen gas bubbled on the headspace above the solution with the stopper installed. The presence of MNSs were validated by confirming their magnetic attraction towards a N50-grade neodymium block magnet with a pull force of 250 lb [33]. The suspension was stored at room temperature, and 1 mL was centrifuged at 20,000× g for 20 min and vacuum-dried for 4 h to determine the concentration (mg/mL).…”
Section: Synthesis Of Magnetic Nanoparticles (Mnps)mentioning
confidence: 99%